Oral hygiene awareness among the adult rural population of district Rewari: a cross-sectional study - ., Anjali; Yadav, Preeti; Yadav, Pooja (International Journal Of Community Medicine And Public Health, 2022)
Background: Aim of the study is to assess the awareness regarding general oral hygiene practices amongst the adult rural population of district Rewari, with the objective to collect the baseline data about the level of awareness regarding oral hygiene amongst the adult rural population of district Rewari, Haryana and help policymakers implement new programs to improve the general health of individuals. Methods: A cross-sectional study was conducted in Rewari district in November 2021. 600 participants were interviewed, data were analyzed using a statistical package for the social science (SPSS) version 21.0 (IBM Corp., Armonk, NY, USA). The frequency distribution tables were prepared to present overall and subgroups data. Categorical variables were compared using the Chi-square test. If the expected frequency is less than 5, Fisher’s exact test was used. P<0.05 was considered statistically significant. Results: There were 52.8% females and 47.2% of males who were interviewed, 97.3% of participants clean their oral cavity. Around 76.1% of population uses brush and 12.1% of participants uses datun. Majority of participants recognized the fact that oral health is important for general health. Conclusions: Even in the year 2022, there is still lack in appropriate oral health awareness even among the educated group of the society. therefore, new programs should be implemented like camps and health talks to improve oral health of an individual in rural areas of the developing countries to educate and spread knowledge of proper dental care.